MEMBANGKITKAN KEMBALI TARI BEDAYO TULANG BAWANG DI KOTA MENGGALA LAMPUNG - I Wayan Mustika (Humaniora, 2007)
This study aims at reviving the dance of Bedayo Tulang Bawang and exploring the deep elements of the dance. Another objective is to comprehend the implied meaning of the neglected dance through the historical texts and contexts as well as the Menggala’s relevant culture. In the resurgence of the dance, there were obstacles such as the limited data and manuscripts on the dance of Bedayo Tulang Bawang. The only available sources are the dressmakers, the learners, and the people who happen to know the choreography. It is important and necessary to understand the dance because the dance has a deep sense and history in conjunction with the life of the people in Bujung Menggala Kampung, Tulang Bawang Regency.